Human Interface and the Management of Information. Information and Interaction for Learning, Culture, Collaboration and Business, 15th International Conference, HCI International 2013, Las Vegas, NV, USA, July 21-26, 2013, Proceedings, Part III - Yamamoto, Sakae; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The three-volume set LNCS 8016, 8017, and 8018 constitutes the refereed proceedings of the 15th International Conference on Human-Computer Interaction, HCII 2013, held in Las Vegas, NV, USA in July 2013. The total of 1666 papers and 303 posters presented at the HCII 2013 conferences was carefully reviewed and selected from 5210 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers accepted for presentation thoroughly cover the entire field of human-computer Interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. This volume contains papers in the thematic area of human interface and the management of Information, addressing the following major topics: learning, education, and skills transfer, art and cultural heritage, collaborative work, business integration, decision support.
A Hybrid Model For An E-learning System which Develops Metacognitive Skills at Students -- Enhancing Information Systems Users$1 (BKnowledge and Skills Transference through Self-regulation Techniques -- Articulating an Experimental Model for the Study of Game-Based Learning -- Psychophysiological Assessment Tools for Evaluation of Learning Technologies -- An Experimental Environment for Analyzing Collaborative Learning Interaction -- Transparent Digital Contents Sharing for Science Teachers -- Development of a Computer Programming Learning Support System Based on Reading Computer program -- The Display Medium, Academic Major and Sex Effect of High School Students on Visuospatial Abilities Test Performance -- Video Feedback System for Teaching Improvement Using Students$1 (BSequential and Overall Teaching Evaluations -- I See, Please Tell Me More -- Exploring Virtual Agents as Interactive Storytellers -- Gamification of Education Using Computer Games -- New Potential of E-learning by Re-utilizing Open Content Online English Learning System as an Auto-assignment Generator -- Learning by Problem-Posing with Online Connected Media Tablets -- Virtual Experience System for a Digital Museum -- Design of Space for Expression Media with the Use of Fog -- User Interface of Interactive Media Art in Stereoscopic Environment -- A Method of Viewing 3D Horror Contents for Amplifying Horror Experience -- Digital Railway Museum: An Approach to Introduction of Digital Exhibition Systems at the Railway Museum -- CoPI: A Web-based Collaborative Planning Interface Platform -- Estimation of Interruptibility during Office Work based on PC Activity and Conversation -- ARM-COMS: Arm-supported embodied communication monitor system -- Challenges of Social Media Managers -- Digital War Room for Design Requirements for Collocated Group Work Spaces -- Detection of Division of Labor in Multiparty Collaboration -- Role of assigned persona for computer supported cooperative work in remote control environment -- Development of a System for Communicating Human Factors Readiness -- A Method for Service Failure Effects Analysis based on Customer Satisfaction -- Searching blog sites with product reviews -- Usability Evaluation of Comprehension Performance and Subjective Assessment on Mobile Text Advertising -- On Services and Insights of Technology Intelligence System -- Sales Strategy Mining System with Visualization of Action History -- An automatic classification of Product review Into given viewpoints -- User Needs Search Using Text Mining -- Finding a Prototype Form of Sustainable Strategies for the Iterated Prisoners Dilemma -- The Study to Clarify The Type of (3z(BOtome-game(3y (BUser -- Integrating the Anchoring Process with Preference Stability for Interactive Movie Recommendations.s
Keywords: Computer science; Information storage and retrieval systems; Education; Computer Science; User Interfaces and Human Computer Interaction; Computer Applications; Computers and Education; Models and Principles; Information Systems Applications (incl. Internet).; Information Storage and Retrieval